Peak Oxygen Uptake in Chronic Fatigue Syndrome/Myalgic Encephalomyelitis: A Meta-Analysis - Franklin, John Derek; Atkinson, Greg; Atkinson, Janet M.; Batterham, Alan M. (International Journal of Sports Medicine, 2019)
To evaluate the magnitude of the difference in VO2peak between patients with Chronic Fatigue Syndrome/ Myalgic Encephalomyelitis (CFS/ME) and apparently healthy controls, 7 databases (Cochrane, PubMed, PsycINFO, Web of Knowledge, Embase, Scopus, Medline) were searched for articles published up to March 2018. Search terms included “chronic fatigue syndrom*”AND (“peak” OR “maxim*” OR “max”) AND (“oxygen uptake” OR “oxygen consumption” OR “VO2peak” or “VO2max”. Eligibility criteria were adults>18 y with clinically diagnosed CFS/ME, with VO2peak measured in a maximal test and compared against an apparently healthy control group. The methodological quality of included studies was assessed using a modified Systematic Appraisal of Quality for Observational Research critical appraisal framework. A random effects meta-analysis was conducted on 32 cross-sectional studies (effects). Pooled mean VO2peak was 5.2 (95% CI: 3.8–6.6) ml.kg−1min−1 lower in CFS/ME patients vs. healthy controls. Between-study variability (Tau) was 3.4 (1.5–4.5) ml.kg−1min−1 indicating substantial heterogeneity. The 95% prediction interval was −1.9 to 12.2 ml.kg−1min−1. The probability that the effect in a future study would be>the minimum clinically important difference of 1.1 ml.kg−1min−1 (in favour of controls) was 0.88 – likely to be clinically relevant. Synthesis of the available evidence indicates that CFS/ME patients have a substantially reduced VO2peak compared to controls.
Keywords: chronic fatigue syndrome; peak oxygen uptake; maximal oxygen uptake; VO2peak